Mechanical properties of rice husk-recycled polypropylene composite / Umar Iqqbal Al-Biruni Mohd Adnan ... [et al.] - Mohd Adnan, Umar Iqqbal Al-Biruni; Rashiddy Wong, Freddawati; Morni, Mohamad Firhan; Abdullah, Abdul Hakim; Abd Rashid, Amirul; Soon, Kong Yong (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
The growing amount of plastic and food waste has become a serious problem around the worldwide. As a byproduct of milling rice, rice husk is an agricultural waste that is produced in bulk quantities. Rice husk has been used as filler in polymer composites in a variety of ways. However, there have only been a few reports of using rice husk as reinforcement in composites made of recycled polypropylene. The limited interfacial reaction between natural fibre and polymer is the fundamental issue in natural fibre-based composites. This prompted the development of sustainable composite manufactured from recycled polypropylene(rPP) and rice husk (RH). Thus, we investigated the intermolecular adhesion between rPP–RH composite with maleic anhydride grafted polypropylene (MAPP) as a coupling agent. Varied compositions of RH in the range of 10–40 wt% with 4 wt% of MAPP were fabricated. The rPP, RH and MAPP were blended and executed in injection moulding. The mechanical properties will be analysed through differential scanning calorimetry, rheology, tensile, flexural, impact and hardness tests. The result shows RH agglomeration and limited dispersion in the composite cause a reduction of up to 40% for tensile strength compared to neat rPP. Despite this, it demonstrates improvements in tensile modulus, flexural modulus, impact, and hardness. It is evidence of a good intermolecular between rPP matrix and RH. In conclusion, the ideal RH loading for composites occurs at a filler content of 40% and has acceptable mechanical properties for various composite applications.